The world of microRNAs of the hepatobiliary system - A.E. Abaturov; V.L. Babуch (Zaslavsky O.Yu., 2021)
The scientific review presents the significance of the world of microRNAs of the hepatobiliary system. For writing the article, information was searched using Scopus, Web of Science, MedLine, PubMed, Google Scholar, EMBASE, Global Health, The Cochrane Library, CyberLeninka databases. It is emphasized that microRNAs in cells play an important role in regulating the activity of gene expression and control numerous physiological processes, such as metabolism, proliferation, differentiation, apoptosis of cells. The association of some diseases with changes in the content of microRNAs in the peripheral bloodstream is shown. The article presents a brief description of the group of non-coding RNAs. The characteristic of the basic microRNA databases with display of electronic addresses is given. Both traditional methods based on amplification technology and new detection methods (next-generation sequencing, electrochemical detection based on enzyme signal amplification, identification by ligation and application of gold nanoparticles) are used to determine microRNAs. The authors compare different methods of microRNA detection. It is noted that overexpression or inhibition of the generation of specific microRNAs is accompanied by impaired liver function and the development of diseases of the hepatobiliary system. Changes in some microRNAs in serum or liver tissue have been shown to be highly diagnostic markers of some liver diseases. Thus, the identification of changes in the level of representativeness of certain microRNAs may have valuable diagnostic information to the practitioner, and the impact on the processes of formation and maturation of microRNAs by drugs is a new direction in the treatment of a wide range of diseases. The modern idea of the diagnostic value of microRNAs in diseases of the biliary tract in children and the possibilities of drug management of the activity of the process of their generation are of particular interest.